2023
DOI: 10.3389/fpls.2022.1065872
|View full text |Cite
|
Sign up to set email alerts
|

Gene coexpression analysis reveals key pathways and hub genes related to late-acting self-incompatibility in Camellia oleifera

Abstract: IntroductionSelf-incompatibility (SI) is an important strategy for plants to maintain abundant variation to enhance their adaptability to the environment. Camellia oleifera is one of the most important woody oil plants and is widely cultivated in China. Late acting self-incompatibility (LSI) in C. oleifera results in a relatively poor fruit yield in the natural state, and understanding of the LSI mechanism remains limited. MethodsTo better understand the molecular expression and gene coexpression network in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Based on different splicing modes, AS can be classified into five categories: skipping exon (SE), retained intron (RI), mutually exclusive exon (MXE), alternative 5′ splice site (A5SS), and alternative 3′ splice site (A3SS). In Camellia oleifera , the variable splicing events are involved in the LSI reaction [ 36 ]. Therefore, we conducted the AS analysis of SP compared with NP in alfalfa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on different splicing modes, AS can be classified into five categories: skipping exon (SE), retained intron (RI), mutually exclusive exon (MXE), alternative 5′ splice site (A5SS), and alternative 3′ splice site (A3SS). In Camellia oleifera , the variable splicing events are involved in the LSI reaction [ 36 ]. Therefore, we conducted the AS analysis of SP compared with NP in alfalfa.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with GSI and SSI, LSI is poorly understood. Transcriptomic analysis of pistils has revealed that LSI is closely associated with Ca 2+ signaling, plant hormone signal transduction, ATP-binding cassette (ABC) transporters, the mitogen-activated protein kinase (MAPK) signaling pathway, reactive oxygen species (ROS) metabolism, PCD-related genes, ubiquitin-mediated proteolysis, and the phosphatidylinositol signaling system [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seed number per fruit was approximately 1.58-9.14 in 118 C. oleifera germplasm resources (Lin et al, 2022), and 102 of them had less than five seeds per fruit. Self-incompatibility may result in ovule abortion to some extent (Liao, 2013;Liao et al, 2014;Gao, 2017;He et al, 2020;Zhou et al, 2020;Li et al, 2023). Moreover, it was found that the infertile ovules that presented when embryonic sac matured, instead of developing after pollination, were another source of abortion ovules (Gao, 2017).…”
mentioning
confidence: 99%